2011
DOI: 10.1007/s12298-011-0058-6
|View full text |Cite
|
Sign up to set email alerts
|

AFLP assessment of genetic diversity among Indian Mucuna accessions

Abstract: Amplified fragment length polymorphism (AFLP) marker was used to assess diversity in germplasm collection of Mucuna species which has gained tremendous attention in the recent past due to its promising nutritional, agronomic and medicinal attributes. Twenty five accessions comprising five species, collected from seven states of India were evaluated with twelve AFLP primer combinations that generated a total of 1,612 fragments with an average of 134 fragments per primer combination. The values of polymorphic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 26 publications
(24 reference statements)
3
5
0
Order By: Relevance
“…All the primer combinations were attributed with resolving power (Rp) ranging from 30 to 40 (average 35.90 ± 4.95). The high values of GD, MI, and Rp are in agreement with the fairly good discriminatory potential of efficient AFLP markers (Behera et al, 2008;Blignaut et al, 2013;Kesari et al, 2010;Laurentin, 2009;Sathyanarayana et al, 2011). A significant positive correlation was noticed among MI, Rp, and GD with coefficients of determination (R 2 ) = 0.991 (MI and Rp), 0.924 (GD and MI), and 0.868 (GD and Rp).…”
Section: Resultssupporting
confidence: 69%
“…All the primer combinations were attributed with resolving power (Rp) ranging from 30 to 40 (average 35.90 ± 4.95). The high values of GD, MI, and Rp are in agreement with the fairly good discriminatory potential of efficient AFLP markers (Behera et al, 2008;Blignaut et al, 2013;Kesari et al, 2010;Laurentin, 2009;Sathyanarayana et al, 2011). A significant positive correlation was noticed among MI, Rp, and GD with coefficients of determination (R 2 ) = 0.991 (MI and Rp), 0.924 (GD and MI), and 0.868 (GD and Rp).…”
Section: Resultssupporting
confidence: 69%
“…To detect the best primer combination for AFLP marker classification of germplasm, several researchers have employed GD, PIC, EMR and MI (Kim et al, 2013;Anderson et al, 1993;Sathyanarayana et al, 2011) The highly significantly correlation with GD and PIC (r 2 =0.999) in the present study agreed with the studies of Sathyanarayana et al (2011) and Kim et al (2013). In addition, Sathyanarayana et al (2011) defined MI as a measure of maker diversity. Like we also found a significant (P≤0.05) positive correlation with GD and PIC in this study.…”
Section: Discussionsupporting
confidence: 84%
“…The RAPD primer RPI-B11 and the SSR primer S16 were found to be the most informative primers to discriminate the sesame genotypes. A higher value for the marker attributes is critical for considering use of the dominant (RAPD and AFLP) and codominant markers (SSR and RFLP) for classification, fingerprinting, genetic diversity analysis, gene mapping, molecular breeding, and germplasm evaluation (Sathyanarayana et al 2011). On comparative basis, we found that GD was almost similar for both RAPD (0.229) and SSR (0.230).…”
Section: Discussionmentioning
confidence: 99%